O09.6 CD4 Below 500: Increase of ART Patients and the Financial Impact in Brazil. (13th July 2013) - Silva, F Viegas Neves da; Guimarães, A; Hallal, R; Greco, D
Abstract : Background: In 2012 the Brazilian Ministry of Health began discussing early treatment for patients with CD4 from 350 to 500. This recommendation aimed to increase the quality of life for PLVIH in Brazil. One of the concerns was the financial impact and the increased number of patients that would access the health system. Methods: To identify the number of PLVIH eligible we extracted from SISCEL's (a Brazilian centralised Laboratory Exams Control System) databank data of the patients with at least one CD4 test (in 2010, 2011 and 2012) between 350 and 500. SISCEL only includes patients on follow up within the public network of laboratories (currently 100 CD4 Laboratories). Around 75% of patients are on follow up in SISCEL. Additionally, to remove patients already on ART we crossed 2 databanks - the SISCEL with the SICLOM (a Brazilian centralised Drugs Control Logistic System). On the other hand, to identify the cost of initial ART, from the total of 1.395 currently dispensed, we selected the seven most used(AZT/3TC+EFV; AZT/3TC+LPV/r; TDF+3TC+EFV; AZT/3TC+ATV+RTV; AZT/3TC+NVP; TDF+3TC+ATV+RTV; TDF+3TC+LPV/r) that represent 91.5% of the initial treatment regimens. Results: There is a cumulative number of approximately 35.221 patients that are eligible for the new recommendation that are being monitored with a potential increase of up to 25% of the patients that are not in SISCEL. The proportional increase in the annual expenditure of ARVs would be of around 43 million dollars (10% increase in the total annual budget for ARVs of around 415 million dollars). Conclusion: From the data above we can conclude that a 10% increase in budget is a small expenditure in comparison to the potential benefits of early ART such as avoiding opportunistic infections, improving quality of life, diminishing costs of hospitalisation, increasing survival rate and diminishing risk of transmission.